Perda dentária e uso de prótese total removível: percepção entre usuários do serviço de saúde de Belo Horizonte - Lara Melina Leite Lima de Paula (2018)
Tooth loss and use of complete dentures: perception among weares of the Belo Horizonte health service Although the prevalence of complete tooth loss has declined in recent decades, there is a considerable proportion of edentulous individuals worldwide associated with the living and health conditions of the population. Edentulism impacts on oral function, which can lead to nutritional loss, aesthetic and psychological, with reductions in selfesteem and social integration. Complete dentures rehabilitation can represent a return to socially accepted standards and contribute to an improvement in people's quality of life and self-esteem. This study aimed to evaluate the perception of users of removable dentures complete offered by the public health service about the subjectivity that involves the course from tooth loss to rehabilitation with removable complete dentures and the process of adaptation to this type of rehabilitation to do so. To do so, a qualitative approach was used with eleven individuals who received their prosthesis through the public health service of Belo Horizonte. These were based on three preestablished topics: (i) losing teeth, (ii) living without teeth and (iii) living with dentures, where the study subjects were the users who obtained their total dentures offered by Primary Health Care in Belo Horizonte.The material was collected through individual interviews with the subjects. The content of the interviews was recorded and later transcribed for analysis. The content analysis was done following the methodological orientation of Graneheim and Lundman. Through this study it was concluded that in the majority of cases, the interviewees reported the pain as a reason for tooth loss, the extraction being the definitive solution for the relief of the problem. Conformism and resignation with the loss of teeth reflect the understanding that edentulism is something natural and inevitable. Living without teeth has been felt by many as a "thud" that affects appearance, chewing, socialization and contributes to food selection. The condition of edentulism generated a feeling of shame, aging and / or inequality. Rehabilitation with prosthesis was seen as something perennial, which returns selfesteem and favors chewing, socialization and feeling of completeness. Although the use of the prosthesis could be felt by many as a nuisance for pain and problems with retention and stability, resignation of suffering favors adaptation. The course from loss to rehabilitation involves positive and negative feelings modulated by the resignation and need to recover normality, the socioeconomic context defined choices and ways of experiencing similar problems by people and influenced in the beliefs and behaviors that resulted in edentulism.